2020
DOI: 10.1080/13880209.2020.1818793
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology, toxicity and pharmacokinetics of acetylshikonin: a review

Abstract: Context: Acetylshikonin, a naphthoquinone derivative, is mainly extracted from some species of the family Boraginaceae, such as Lithospermum erythrorhizon Sieb. et Zucc., Arnebia euchroma (Royle) Johnst., and Arnebia guttata Bunge. As a bioactive compound, acetylshikonin has attracted much attention because of its broad pharmacological properties. Objective: This review provides a comprehensive summary of the pharmacology, toxicity, and pharmacokinetics of acetylshikonin focussing on its mechanisms on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Known mechanisms of action are the inhibition of cell proliferation, induction of apoptosis, and reduction of cell migration and invasion potential through a variety of molecular signal transduction pathways [ 12 , 13 ]. Acetylshikonin, another promising naturally occurring shikonin derivative, have also several pharmacological effects [ 14 ]. In addition, attempts have been made to optimize antitumorigenic activity by modulating the structure of naturally occurring shikonin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Known mechanisms of action are the inhibition of cell proliferation, induction of apoptosis, and reduction of cell migration and invasion potential through a variety of molecular signal transduction pathways [ 12 , 13 ]. Acetylshikonin, another promising naturally occurring shikonin derivative, have also several pharmacological effects [ 14 ]. In addition, attempts have been made to optimize antitumorigenic activity by modulating the structure of naturally occurring shikonin derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…To study the effects of shikonin and its derivatives ( Figure 1 A) in healthy chondrocytes (HC) and primary OA chondrocytes (pCH-OA), cells were treated with various concentrations of the compounds of interest, and the dose-response relationship was analyzed. Shikonin and acetylshikonin are naturally occurring shikonin derivatives [ 15 , 16 , 17 ]. Cyclopropylshikonin was synthesized in a previous study and found to be the most cytotoxic compound out of a screening of novel shikonin derivatives [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of action included, for example, inhibition of cell proliferation, induction of apoptosis, and reduced cell migration and invasion through a variety of molecular signal transduction pathways. Another promising, naturally occurring shikonin derivative is acetylshikonin, which has also been reported to possess several pharmacological activities [ 15 , 16 , 17 ]. Furthermore, several attempts have been made to optimize the naturally occurring shikonin derivatives by modulating the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Trolox equivalent antioxidant capacity was determined, which yielded values of 131.05 and 1407.24 μM TE/ mg extract using DPPH and ABTS tests, respectively (Table 2). This extract was proven to include a number of well-known antioxidants, including cinnamic acid derivatives [29], and acetylshikonin [30]. Despite this, antagonism between substances in the plant mixture could explain the mild effect [31].…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%